Digitalisation - ‘The Invisible Hand’ of Digital economy - Edi-Cristian Dumitra; Iulia Maria Gândea (Revista de Studii Financiare, 2022)
This paper explores the way in which digitalisation might be considered the metaphor of ‘The Invisible Hand’ for the current economic environment, in which the paradigm of economics has been shifted towards a Digital economy and the transition has been accelerated by the crisis determined from the recent COVID-19 pandemic. Therefore, the mainstream of Classical economics has been replaced by digital activities based on the development of digital technologies, both as goods and services, production processes, and infrastructure. As a fast solution for recovering after the difficult period, many businesses have implemented digital technologies in their business models and strategies. Hence, the present paper collects information available from the scientific literature, creating a brief overview of digitalisation, the Digital economy, and the role of digitalisation in developing the Digital economy. Moreover, the metaphor is explained as digitalisation represents the driver for business development, achieving sustainable business strategies, implementing innovative business models for higher revenues, and reshaping the economic environment. The methodology used by the authors is the review of scientific literature relevant to the research, approaching the main ideas exposed, and exploring them for conclusions and further discussions.